The cyclicality of international public sector borrowing in developing countries: Does the lender matter? - Arturo José Galindo Andrade; Ugo Panizza (Inter-American Development Bank (IDB), 2017)
The paper shows that international government borrowing from multilateral development banks is countercyclical while international government borrowing form private sector lenders is procyclical. The countercyclicality of official lending is mostly driven by the behavior of the World Bank (borrowing from regional development banks tends to be acyclical). The paper also shows that official sector lending to Latin America and East Asia is more countercyclical than official lending to other regions. Private sector lending is instead procyclical in all developing regions. While the cyclicality of official lending does not depend on domestic or international conditions, private lending becomes particularly procyclical in periods of limited global capital flows. By focusing on both borrower and lender's heterogeneity the paper shows that the cyclical properties of international government debt are mostly driven by credit supply shocks. Demand factors appear to be less important drivers of procyclical international government borrowing. The paper's focus on supply and demand factors is different from the traditional push and pull classification, as push and pull factors could affect both the demand and the supply of international government debt.
Keywords: E62; F34; F32; 330; International Government Debt; Capital Flows; Fiscal Policy; International Financial Institutions